PENGARUH PERPUTARAN PIUTANG DAN KEBIJAKAN HUTANG TERHADAP NILAI PERUSAHAAN PADA PT INDOFOOD SUKSES MAKMUR TBK PERIODE 2013 - 2022 - Irhamna, Rifka; Noryani (Journal of Research and Publication Innovation, 2024)
The aim of this research is to determine the influence of accounts receivable turnover and debt policy on company value at PT Indofood Sukses Makmur Tbk for the 2013 - 2022 period, using quantitative methods. The type of data used is secondary data obtained from the published financial reports of PT Indofood Sukses Makmur Tbk for the 2013 - 2022 period. Data analysis uses descriptive tests, classic assumption tests including normality tests, multicollinearity tests, heteroscedasticity tests, autocorrelation tests, multiple linear regression analysis, analysis of the coefficient of determination, hypothesis testing includes partial tests (T test) and simultaneous tests (F test). Data processing uses SPSS Version 26. The research results of accounts receivable turnover have a significant effect on company value. That Tcount is 3.228 > Ttable is 2.364 and is significant at 0.014<0.05 so that Ho is rejected and H1 is accepted. The results of research on debt policy do not have a significant effect on company value. That Tcount is - 1.090 < Ttable is 2.364 and is significant 0.312> 0.05 so that Ho is accepted and H2 is rejected. The results of research on receivables turnover and payables policy have a significant effect on company value. That the value of Fcount is 29.684 while Ftable is 4.74. So Fcount is 5.298>Ftable 4.74 and is significantly smaller than 0.05, namely .040<0.05. So it can be said that Ho is rejected and H3 is accepted. Keywords: Receivables Turnover, Debt Policy, Company Value